The invisibility of covert bullying among students: Challenges for school intervention - Barnes, Amy (2012)
Covert bullying behaviours are at least as distressing for young people as overt forms of bullying, but often remain unnoticed or unacknowledged by adults. This invisibility is increased in schools by inattention to covert bullying in policy and practice, and limited staff understanding and skill to address covert behaviours. These factors can lead to a school culture that appears to tolerate and thus inadvertently encourages covert bullying. This study explores these dynamics in Australian primary and secondary schools, including the attitudes of over 400 staff towards covert bullying, their understanding of covert bullying behaviours, and their perceived capacity to address these behaviours both individually and at a whole-school level. While most respondents felt a responsibility to intervene in bullying situations, nearly 70% strongly agreed with statements that staff need more training to address covert bullying. Only 10% of respondents described their current whole-school strategies as very effective in reducing covert bullying, and fewer than 40% reported their school had a bullying policy that explicitly referred to covert bullying. These results suggest an urgent need for sustainable professional development to enhance school staff understanding, skills and self-efficacy to address covert bullying through school policy and practice, and the need to identify and consolidate effective strategies to better address these behaviours